Bilateral pulmonary embolism and ilio-femoral DVT associated with recent amputation of lower limb, long distance air travel and suspected thrombophilia. - Faruq, Mohammad Omar; Hayat, Syed Muhammad Shahin ur; Karim, Rezaul; Salam, Tahsin; Sardar, Aslam Uddin; Kabir, Faisal; Khan, Arifur Rahman; Gafur, Dewan Muhammad Mahmudul; Syam, Mohammad; Arefin, AKM Nahid; Choudhury, Shamima (Bangladesh Critical Care Journal, 2016)
We present a 36 years old Bangladeshi male, known smoker, while working in Bahrain, suffered from arterial thromboembolism on left lower extremity resulting in gangrene of left leg. He underwent above knee amputation of the affected limb. After 16 days stay in the hospital with an open amputated stump wound, he was sent back to Bangladesh by air. While in the airplane, he complained of chest discomfort about two hours before landing at Dhaka airport of Bangladesh. Following disembarkation he was admitted into local cardiac hospital where a diagnosis of left ventricular failure with unstable angina was made. Five days later he was transferred to ICU of Ibn Sina Hospital for better management. Patient had high serum D-dimer level and fibrin degradation products (FDP) level. negative antinuclear antibody (ANA) test, negative anti-cardiolipin antibody test, normal troponin I, Homocysteine, antithrombin III, protein S, & protein C levels. Initial X-ray chest showed left lower zone wedge shaped density. ECG showed sinus tachycardia. CT angiogram of chest showed bilateral pulmonary embolism (PE) and large left pleural effusion. Contrast CT abdomen showed bilateral iliac vein thrombus extending to lower inferior vena cava. Left pleural effusion was found to be grossly hemorrhagic. Patient was treated with low molecular weight heparin and warfarin. As thrombolysis was not feasible, he was advised to have thrombo-embolectomy. He refused surgical option and left hospital against medical advice. This case illustrates that multiple risk factors can be responsible for PE, and appropriate & timely interventions are always needed to prevent morbidity and or mortality Bangladesh Crit Care J March 2016; 4 (1): 46-50